Review of Euchromadorinae (Nematoda: Chromadorida) with description of a new species of Trochamus Boucher & De Bovée, 1971 from the Sundarban, India - Datta, Tridip Kumar; Al-Helal, Md. Abdullah (Zootaxa, 2023)
Diagnostic characters for all 11 valid genera of Euchromadorinae are presented with taxonomic key on the basis of morphology of male copulatory apparatus, cuticular pattern, amphideal fovea, and buccal onchia. The key to the species of Trochamus spp. is also constructed with the description of T. timmi sp. n. from the mud-flat of Sundarban, India. The newly described species is different from other Trochamus spp. on the basis of the appearance of lateral differentiation of cuticle, long curved spicule, simple gubernaculum and the presence of pre-cloacal modification in male.